Experiences of Muslims in India on digital platforms with anti-Muslim hate: a culture-centered exploration - Dutta, Mohan J.; Pal, Mahuya (Frontiers in Communication, 2024)
This manuscript examines the experiences of Muslims in India with hate on digital platforms. Extant research on Islamophobia on digital platforms offers analyses of the various discourses that circulate on digital platforms. This manuscript builds on that research to document the experiences of online hate among Muslims in India based on a survey of 1056 Muslims conducted by Qualtrics, a panel-based survey company, between November 2021 and December 2021. The findings point to the intersections between white supremacist and Hindutva alt-right messages on digital platforms. Moreover, they document the extensive exposure of Muslims in India to Islamophobic hate on digital platforms. The paper wraps up with policy recommendations regarding addressing online Islamophobic hate on digital platforms.